Auditoría de Gestión al Área de Talento Humano de la Cooperativa de Ahorro y Crédito Crediamigo Ltda. Período 2015 - Calderón Encarnación, Mónica Gabriela (2017)
The development of the thesis: "MANAGEMENT AUDIT TO THE HUMAN TALENT AREA OF THE COOPERATIVE OF AHORRO Y CREDITO CREDIAMIGO LTDA., PERIOD 2015", is oriented to the application of the Management Audit, to establish the degree of control that maintains The Cooperative in administrative and operational activities, through the application of indicators to measure the efficiency, effectiveness and economy with which resources are handled, the research work will enable the verification of compliance with Laws, Norms and Regulations in the development Of the activities and issue a report containing comments conclusions and recommendations the same ones that must be fulfilled for the development of the Cooperative. In order to comply with the first objective, Phase I was the Preliminary Knowledge, where the evaluation of the internal control structure was applied, which allowed us to accumulate information about the operation of the existing controls in the Cooperative. The second objective is to develop it through the application of investigative techniques such as observation and the questionnaire applied to the employees of the Cooperative, in order to obtain the real and timely information of the components audited. To achieve the third objective, indicators of efficiency, effectiveness and economy were used to assess the 5 degree of compliance with the planned activities, followed by comments, conclusions and recommendations to take corrective measures to help achieve the goals and objectives . As a final objective, a report containing comments, conclusions and recommendations was presented, with the purpose of publicizing all relevant aspects, so that they can take corrective measures.